2021
DOI: 10.1159/000513553
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hyperoxia-Induced Lung Injury from Associated Intestinal and Lung Dysbiosis in Neonatal Mice

Abstract: Background: Preclinical studies have demonstrated that hyperoxia disrupts the intestinal barrier, changes the intestinal bacterial composition, and injures the lungs of newborn animals. Objectives: The aim of the study was to investigate the effects of hyperoxia on the lung and intestinal microbiota and the communication between intestinal and lung microbiota and to develop a predictive model for the identification of hyperoxia-induced lung injury from intestinal and lung microbiota based on machine learning a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Other studies have shown decreased Proteobacteria and increased Actinobacteria in the lung microbiota from newborn mice due to hyperoxia exposure 9 . Furthermore, hyperoxia altered alpha diversity in lung microbiota of neonatal mice and facilitated translocation of gut microbiota to the lungs, which activated lung inflammation 51 …”
Section: Alterations Of the Lung And Gut Microbiota Associated With Bpdmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have shown decreased Proteobacteria and increased Actinobacteria in the lung microbiota from newborn mice due to hyperoxia exposure 9 . Furthermore, hyperoxia altered alpha diversity in lung microbiota of neonatal mice and facilitated translocation of gut microbiota to the lungs, which activated lung inflammation 51 …”
Section: Alterations Of the Lung And Gut Microbiota Associated With Bpdmentioning
confidence: 95%
“…Briefly, gut dysbiosis increases intestinal permeability, thereby facilitating bacterial translocation directly to the lungs 6,51 . Moreover, microbiota dysbiosis produces polysaccharide A, sphingolipids, and other metabolites that are recognized by immune cells, leading to local or systemic inflammation and metabolic disturbances 52 .…”
Section: Possible Mechanisms Of Gut Microbiota Influencing Bpdmentioning
confidence: 99%
“…Differential gene enrichment analysis showed that glycan biosynthesis and metabolism were among the top three metabolic pathways with significant differences [ 144 ]. Chen et al reported that intestinal bacteria were present in the lungs of hyperoxia-induced neonatal mice, suggesting that hyperoxia could alter the microbiota of the intestine and lungs and promote bacterial translocation from the intestine to the lungs [ 145 ]. Moreover, Wedgwood et al showed that hyperoxia-induced PH exhibits intestinal dysbiosis and can be attenuated by the administration of Lactobacillus [ 146 ].…”
Section: Potential Pathogenesis Of Metabolic Reprogramming In Hyperox...mentioning
confidence: 99%
“…As our group and others have previously shown, increased proteobacteria in the lungs can upregulate the activity of matrix metalloproteinase 9 (MMP-9), leading to progressive lung tissue damage and the development of chronic lung diseases [7][8][9][10][11][12][13][14][15]. This cascade results in collagen degradation generating tripeptide N-acetyl proline-glycine-proline (Ac-PGP), a potent neutrophil chemoattractant [9,10,[16][17][18]. Neutrophilic inflammation is a common feature of many chronic lung diseases, and other cytokines including C-reactive protein (CRP) may contribute to neutrophil recruitment and increased inflammatory response [19][20][21].…”
Section: Introductionmentioning
confidence: 99%